Can mental health and readjustment be improved in UK military personnel by a brief period of structured postdeployment rest (third location decompression)?. Issue 7 (26th February 2013) - Jones, Norman; Jones, Margaret; Fear, Nicola T; Fertout, Mohammed; Wessely, Simon; Greenberg, Neil
Abstract : Objective: Third Location Decompression (TLD) is an activity undertaken by UK Armed Forces (UK AF) personnel at the end of an operational deployment which aims to smooth the transition between operations and returning home. We assessed whether TLD impacted upon both mental health and postdeployment readjustment. Method: Data collected during a large cohort study was examined to identify personnel who either engaged in TLD or returned home directly following deployment. Propensity scores were generated and used to calculate inverse probability of treatment weights in adjusted regression analyses to compare mental health outcomes and postdeployment readjustment problems. Results: TLD had a positive impact upon mental health outcomes (post-traumatic stress disorder (PTSD) and multiple physical symptoms) and levels of harmful alcohol use. However, when the samples were stratified by combat exposure, although postdeployment readjustment was similar for all exposure levels, personnel experiencing low and moderate levels of combat exposure experienced the greatest positive mental health effects. Conclusions: We found no evidence to suggest that TLD promotes better postdeployment readjustment; however, we found a positive impact upon alcohol use and mental health with an interaction with degree of combat exposure. This study suggests that TLD is a useful postdeployment transitional activity that may help to improve PTSD symptoms and alcohol use in UK AF personnel.